Infection following fractures of the proximal tibia – a systematic review of incidence and outcome - Henkelmann, Ralf; Frosch, Karl-Heinz; Glaab, Richard; Lill, Helmut; Schoepp, Christian; Seybold, Dominik; Josten, Christoph; Hepp, Pierre (BMC musculoskeletal disorders, 2017)
To systematically review all available studies of operatively treated proximal tibia fractures and to report the incidence of superficial or deep infection and subsequent outcomes. A systematic review of the literature in Medline, Cochrane, Embase and GoogleScholar was conducted to identify studies with cohorts of patients with infection after surgical treatment of proximal tibia fractures. Studies were included according to predefined inclusion and exclusion criteria. The studies were analysed for methodological deficiencies and quality of outcome reporting based on the Level of Evidence (LOE) and Coleman Methodology Scoring (CMS.) RESULTS: In total 32 studies were included. There was heterogeneity between the studies, in terms of subject of the studies, outcome criteria, fracture type and classification, surgical techniques and length of follow-up. Therefore, no meta-analysis could be performed. The average CMS was 54.2 (range 36-75). The included studies were 25 case series (LOE IV), 6 were prospective cohort studies (LOE III) and one was a prospective randomized trial (LOE I). 203 (12.3%, range: 2.6-45.0%) infections occurred in the overall population (n = 2063). Those were divided into 129 deep infections and 74 superficial infections. Revision due to infection was reported in 29 studies, microbiological results in 6, respectively. 72 (55,8%) of 129 cases reporting outcome after deep infection had an unsatisfactory outcome with substantial limitations of the affected joint and leg. Postoperative infections are a challenge, sometimes requiring several revisions and often with a worse outcome. Further studies with structured study protocols should be performed for a better understanding of risk factors to improve treatment outcomes.